Analyzing popular music - Moore, Allan F. (Cambridge University Press, 2003)
How do we "know" music? We perform it, we compose it, we sing it in theshower, we cook, sleep and dance to it. Eventually we think and write about it. This book represents the culmination of such shared processes. Each of these essays, written by the leading writers on popular music, is analytical in some sense, but none of them treats analysis as an end in itself. The book represents a wide range of genres (rock, dance, TV soundtracks, country, pop, soul, easy listening, Turkish Arabesk) and deals with issues as broad as methodology, modernism, postmodernism, Marxism and communication. It aims to encourage listeners to think more seriously about the "social" consequences of the music they spend time with and is the first collection of essays to incorporate contextualisation in this way.--Publisher's description